1997
DOI: 10.20965/jaciii.1997.p0062
|View full text |Cite
|
Sign up to set email alerts
|

Mission Planning and Flight Control: Meeting the Challenge with Intelligent Techniques

Abstract: This paper presents a hybrid hardware/software platform that supports flight control and mission planning algorithms for an autonomous helicopter. The emphasis is on the use of intelligent fuzzy logic based techniques and an object-modeling approach to account for unmodeled dynamics to address uncertainty issues and to provide a flexible platform for development purposes and an operator interface. Fuzzy logic routines are implemented in such critical vehicle modules as the route planner the fuzzy navigator the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The mission adaptation component via state or waypoint parameter adaptation enables the system/aircraft to accomplish an altered yet admissible mission. Changes to the parameters can be implemented within the receding window employed by the middle level control redistribution or path re-planning stage [21]- [25].…”
Section: High-level Flight / Mission Adaptationmentioning
confidence: 99%
“…The mission adaptation component via state or waypoint parameter adaptation enables the system/aircraft to accomplish an altered yet admissible mission. Changes to the parameters can be implemented within the receding window employed by the middle level control redistribution or path re-planning stage [21]- [25].…”
Section: High-level Flight / Mission Adaptationmentioning
confidence: 99%
“…The prognostics research that is reported in the literature largely focuses on solutions to specific problems, such as electronic prognostics (Vichare and Pecht 2006;Ridgetop Group 2004;Mishra and Pecht 2002;Kalgren et al 2007), vibration analysis (Carden and Fanning 2004;Doebling et al 1996;Catbas and Atkan 2002), helicopter gearbox monitoring (Engel et al 2000;Heng et al 2009;Vachtsevanos et al 1997;Wang and Vachtsevanos 2001;Orchard and Vachtsevanos 2007;Kacprzynski et al 2004), Joint Strike Fighter (JSF) applications (Keller et al 2006;Orsagh et al 2005;Roemer et al 2005;Ferrell et al 1999;Ferrell et al 2000;Smith et al 1997;Hess and Fila 2002;Line and Clements 2005), etc. There are now papers in several major meeting series including the Machinery Failure Prevention Society annual meeting, the IEEE Reliability Society meetings, the PHM Society annual conference, and sessions within application-specific meetings, such as those for aerospace systems.…”
Section: Prognostic Algorithmsmentioning
confidence: 99%
“…Notions of "control" are expanding from the traditional loop-control concept to include such other functionalities as supervision, coordination and planning, situation awareness, diagnostics, and optimization [9]- [11]. Consider, for example, the control system for an uninhabited aerial vehicle (UAV) such as a vertical takeoff and landing (VTOL) UAV of the helicopter type [12].…”
Section: Current Practice In Control System Configurationsmentioning
confidence: 99%